Epidemiological surveillance of blood donors at the University Clinics of Kinshasa, Kinshasa, DR Congo (2019–2022) - Lomamba Lodi, Olivier; Matondo, Blaise S.; Ndona, Yvette N.; Melki, S.; Ibana, Jonathan K.; Lukusa, Franck N. (Orapuh Journal, 2025)
Introduction Blood safety in the Democratic Republic of the Congo (DRC) remains a major challenge due to the risk of transmission of blood-borne infections such as HIV, HBV, HCV, and Treponema pallidum. Despite efforts to improve screening practices, these infections persist among blood donors. Purpose To examine the evolution of the transmission of blood-borne infections among blood donors at the University Clinics of Kinshasa between 2019 and 2022. Methodology This retrospective study analysed data from 3,528 blood donors at the University Clinics of Kinshasa between 2019 and 2022. Donors were tested for serological markers of HIV, HBV, HCV, and Treponema pallidum using immunochromatographic tests and ELISA. Sociodemographic, clinical, and biological data were collected and analysed using SPSS version 26. Results A total of 3,920 blood donations were included, with a prevalence of 2.8% for HBV, 1.9% for HCV, 1.3% for HIV, and 0.8% for syphilis. Annual variations in blood-borne infections were observed. HBV prevalence increased from 3.5% in 2019 to 5.0% in 2021. For HCV, the prevalence decreased from 3.0% in 2019 to 1.1% in 2020 (p < .05). The prevalence of syphilis increased from 0.4% in 2019 to 1.0% and was statistically significant (p < .05). HIV prevalence varied from 1.2% to 1.8% during the study period. Conclusion Despite measurable improvements in screening methods and blood donor safety protocols, residual infection risk remains. It is crucial to improve screening procedures and establish continuous epidemiological monitoring. A multisectoral approach involving health authorities and the community is necessary to enhance blood safety in the DRC.